2015
DOI: 10.1097/hco.0000000000000192
|View full text |Cite
|
Sign up to set email alerts
|

Fetal programming and epigenetic mechanisms in arterial hypertension

Abstract: a,Ã Purpose of reviewTo provide an overview of available evidence of the potential role of epigenetics in the pathogenesis of hypertension and vascular dysfunction. Recent findingsArterial hypertension is a highly heritable condition. Surprisingly, however, genetic variants only explain a tiny fraction of the phenotypic variation and the term 'missing heritability' has been coined to describe this phenomenon. Recent evidence suggests that phenotypic alteration that is unrelated to changes in DNA sequence (ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 33 publications
(34 reference statements)
0
6
0
2
Order By: Relevance
“…-АГ [1,13]. Навколишнє середовище впливає на серцево-судинну систему, може викликати такі патологічні стани, як атеросклероз або інфаркт міокарда [14].…”
Section: основні епігенетичні механізми розвитку артеріальної гіпертеunclassified
See 1 more Smart Citation
“…-АГ [1,13]. Навколишнє середовище впливає на серцево-судинну систему, може викликати такі патологічні стани, як атеросклероз або інфаркт міокарда [14].…”
Section: основні епігенетичні механізми розвитку артеріальної гіпертеunclassified
“…За останні 20 років проведена велика кількість досліджень з вивчення ролі поліморфізмів різних генів-кандидатів у ґенезі захворюван-ня. Однак фенотипічні особливості часто не пов'язані зі змінами послідовності ДНК [1].…”
unclassified
“…In line with this concept, vulnerable periods during early life known to be associated with fetal programming of cardiovascular disease coincide with increased epigenetic activity. The review article by Scherrer et al [8] highlights the potential contribution of fetal programming to the pathogenesis of arterial hypertension: studies in young offspring of mothers suffering from preeclampsia [9] and in apparently healthy children conceived by assisted reproductive technologies (ART) [10,11] have shown that these children display premature vascular aging and increased BP. Studies in animal models of these two entities have shown that epigenetic dysregulation with consequent altered expression of genes important for BP regulation [that is, endothelial nitric oxide synthase (eNOS)] plays a central role in the pathogenesis of arterial hypertension [12,13].…”
mentioning
confidence: 98%
“…In recent years, a considerable number of studies have sought to investigate the epigenetic mechanisms of gene regulation in renal development and function and hypertension (15,20,37,50,53). Epigenetics is defined as the study of the molecular mechanisms that regulate gene expression often leading to reversible changes that can be stable throughout the lifespan of an organism and potentially be heritable (11,40,49). DNA hypermethylation of the RASAL1 gene and dysregulation of miR-132, miR-212, miR-181b, and miR-663 in the RAS are two epigenetic mechanisms that have been studied in the context of hypertension in the kidney (3,4,6,10,28).…”
mentioning
confidence: 99%